MOTOR CREATIVITY ACCORDING TO IDENTIFIED PROBLEM SOLVING - CORTEZ GUTIÉRREZ, HERNÁN ÓSCAR (2024)
INTRODUCTION: THE LEVELS OF PROBLEM SOLVING ALLOW US TO CHARACTERIZE TWO GROUPS, ONE CALLED “APPROPRIATE” AND THE OTHER “NOT APPROPRIATE” THAT CAN SERVE TO IMPROVE THE LEVEL OF CREATIVITY AND ACADEMIC PERFORMANCE OF STUDENTS. THEREFORE, THE DIMENSIONS OF MOTOR CREATIVITY AND THE PROBLEM-SOLVING ABILITIES OF THE TWO GROUPS SHOULD BE INVESTIGATED LONGITUDINALLY AND SPATIALLY IN STUDENTS. METHODOLOGY: TWO PROBLEM-SOLVING GROUPS WERE IDENTIFIED AND STATISTICALLY SIGNIFICANT DIFFERENCES IN THE MEANS BETWEEN THE IDENTIFIED GROUPS WILL BE ESTABLISHED THROUGH AN ANOVA AND/OR MANOVA IN THE MOTOR CREATIVITY SCORES. WE APPLIED SPEARMAN CORRELATIONAL STATISTICS. THE SAMPLE WAS NON-RANDOM AND BASED ON CONVENIENCE. DATA WERE SEGMENTED BY GENDER AND AGE USING SPSS, AND STATISTICAL ANALYZES SUCH AS MULTIPLE REGRESSION, ODDS RATIO (OR), CONFIDENCE INTERVALS (CI) FOR RISKS WERE PERFORMED. NEURAL NETWORKS WERE USED TO EVALUATE THE IMPORTANCE OF THE VARIABLES. RESULTS: DIFFERENCES WERE OBTAINED BETWEEN THE AVERAGE LEVELS OF MOTOR CREATIVITY IN THE TWO PROBLEM-SOLVING GROUPS. THE VERIFICATION OF THE DIFFERENCES IN MEANS IS SUPPORTED BY THE FISHER STATISTIC. PEARSON AND SPEARMAN CORRELATION TESTS INDICATED A SIGNIFICANT RELATIONSHIP BETWEEN MOTOR CREATIVITY AND PROBLEM SOLVING WITH VARIOUS OBJECTS. THE KOLMOGOROV-SMIRNOV TEST CONFIRMED THE NORMAL DISTRIBUTION OF THE VARIABLES. DISCUSSION: FINDINGS SUGGEST THAT MOTOR CREATIVITY IS SIGNIFICANTLY INFLUENCED BY PROBLEM-SOLVING SKILLS, UNDERSCORING THE NEED FOR EDUCATIONAL PROGRAMS THAT INCORPORATE CREATIVE PHYSICAL ACTIVITIES. SIMILAR RESULTS ARE ESTABLISHED WITH MEANS COMPARISON TESTS OF PARAMETRIC (STUDENT'S T) AND NON-PARAMETRIC (MANN-WHITNEY U) TESTS. CONCLUSIONS: IT IS IMPORTANT TO INTERVENE IN THE GROUP CALLED “NOT APPROPRIATE” TO IMPROVE THEIR LEVEL OF MOTOR CREATIVITY. LIKEWISE, MOTOR CREATIVITY IS CLOSELY LINKED TO PROBLEM SOLVING, AND EDUCATIONAL STRATEGIES THAT PROMOTE CREATIVE MOVEMENT CAN SIGNIFICANTLY IMPACT THE COMPREHENSIVE DEVELOPMENT OF STUDENTS. © 2024, HISIN (HISTORY OF INFORMATION SYSTEMS). ALL RIGHTS RESERVED.